Organic Agriculture Comprehension of Soil Agriculture Farmers in Amasya Province of Turkey - Mehmet Aksoy; Başaran Karademir; İbrahim Hakkı Kadirhanoğulları (Turkish Journal of Agriculture: Food Science and Technology)
Organic Agricultural products are natural food products that are checked and certified by authorized institutions at all stages of cultivation and presented to the consumer. In this study, the knowledge and practices of soil agriculture farmers in Amasya province about Organic Agriculture production were investigated by face-to-face survey method. In the survey, the local producers were asked what Organic Agriculture is in general, their status of producing Organic Agriculture, whether they fulfill the Organic Agriculture requirements for Organic Agriculture production. The obtained data were presented numerically and proportionally. Data were also analyzed with the Decision Tree method using the CART (Classification and Regression Tree) algorithm. According to the findings, although the local farmers declared that they knew what Organic Agriculture was at a high level, it was seen that none of the producers fulfilled the requirements of Organic Agriculture in practice. According to the survey data, while the farmers reported that they received the information about Organic Agriculture from TV-radio and the internet to a large extent (58.5%), a very small percentage (11%) stated that they received training. According to this result, it has been concluded that the local farmers do not have enough information about Organic Agriculture, but the lack of information can be easily eliminated via TV-radio and the internet. As a result, it was concluded that Amasya farmers do not have sufficient information about Organic Agriculture production for now, but if appropriate training is provided, successful Organic Agriculture production output can be achieved.